Corneal topographic and aberrometric changes in patients with acquired blepharoptosis after levator resection surgery - Sariyeva Ismayilov, Ayna; Doğanay, Derya; Yelkovan, Muhammed (The European Research Journal, 2025)
Objective: To evaluate changes in corneal topography and aberrometry in patients with acquired blepharoptosis after levator resection surgery. Methods: This prospective, interventional study evaluated 30 eyelids of 19 patients who underwent levator resection surgery for acquired blepharoptosis with fair and good levator function (LF). Patients underwent corneal topography before and 3 months after surgery. Results: Eleven patients had bilateral, and 8 patients had unilateral surgery. There were significant decreases in steep keratometry (K2) (preoperative: 46.21±5.02, postoperative: 44.58±2.11, P=0.046) and corneal astigmatism (preoperative: 2.98±0.61, postoperative: 1.59±1.50, P=0.034). There were no statistically significant differences between the preoperative and postoperative values of flat keratometry (K1) (P=0.585), mean keratometry (Kmean) (P=0.122), axis of corneal astigmatism (P=0.548), central corneal thickness (P=0.350), anterior chamber depth (P=0.747) and anterior chamber volume (P=0.679). The root mean square (RMS)-higher order aberrations (HOA) (P